Is Fibroblast growth factor 23 the leading cause of increased mortality among chronic kidney disease patients? A narrative review - Usama A.A. Sharaf El Din; Mona M. Salem; Dina O. Abdulazim (Journal of Advanced Research, 2017)
The death rate among chronic kidney disease patients is the highest compared to other chronic diseases. 60% of these fatalities are cardiovascular. Cardiovascular calcifications and chronic inflammation affect almost all chronic kidney disease patients and are associated with cardiovascular mortality. Fibroblast growth factor 23 is associated with vascular calcification. Systemic inflammation in chronic kidney disease patients is multifactorial. The role of systemic inflammation in the pathogenesis of vascular calcification was recently reappraised. Fibroblast growth factor 23 was accused as a direct stimulus of left ventricular hypertrophy, uremic inflammation, and impaired neutrophil function. This review will discuss the underlying mechanisms that underlie the link between Fibroblast growth factor 23 and increased mortality encountered among chronic kidney disease patients.